Structural Course of Surah in the Interpretations of the Holy Quran - Abolfazl Khoshmanesh; Fatemeh Aliyan Nezhadi (آموزه‌های قرآنی, 2020)
The division of the Holy Quran into chapters is based on divine wisdom, and attention to it has existed since the beginning of the revelation, as well as in the teachings of the Holy Prophet (PBUH) and the “People of the Household” (AS), with interpretations and from various angles and few people consider this division to be purely accidental and meaningless. Knowing Surah and attention to the structure of chapters is something that has become more and more important in recent times and has been considered as one of the important characteristics of the style and style of the Qur'an and a basis for systematic thinking. Using the descriptive-analytical method and paying attention to what has been done so far in this field, the present article has followed the reflection of the structure and internal communications of the chapters in the interpretations of the Qur'an. Such research explains the position of concepts such as thematic unity, unit comprehensiveness, geometrical structure, structural interpretation, and structural order more and better and shows that the formation and evolution of understanding the structure of the surah can be one of the factors and strategies for deriving concepts from the verses and surahs of the Holy Quran.